Strategi Promosi Pendidikan dalam Meningkatkan Jumlah Peserta Didik Pada MAS Nahdatul Islam Mandau - Mohd. Fikri Azhari; Siti Nurfadhilah (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The purpose of this study is to describe: 1) the implementation of educational promotion strategies in increasing the number of students at MAS. Nahdatul Islam Mandau, 2) the supporting and inhibiting factors of educational promotion strategies in increasing the number of students at MAS. Nahdatul Islam Mandau. The type of research used is qualitative with a case study approach. This research was conducted at MAS Nahdatul Islam Mandau. Data collection techniques were observation, interviews, and documentation. Data analysis techniques included data compression, data display, and drawing conclusions. The results of the study indicate that: 1) the implementation of educational promotion strategies went well in increasing the number of students at MAS Nahdatul Islam Mandau, 2) the supporting and inhibiting factors of educational promotion strategies went well in increasing the number of students at MAS. Nahdatul Islam Mandau. Supporting factors include having a strategic location, affordable madrasah fees, inhibiting factors include imperfect facilities and infrastructure owned by the madrasah, experiencing intense competition, and the existence of an equivalent madrasah aliyah, because rural communities have the mindset that private schools are expensive.